Unusually sited lower third molar. Issue 9 (17th September 2020) - Campbell, Tim; Raffner, Etienne; Danford, Martin; Sloane, James
Abstract : We present the case of a 60-year-old woman who presented to our unit with left-sided facial swelling, pain and trismus. Initially managed as a parotitis by a different specialty, an ultrasound subsequently showed a collection deep to the parotid associated with an ectopic wisdom tooth within the mandibular posterior ramus/condyle and the patient was referred to our department. After treating the acute infection, the wisdom tooth was surgically removed. Our case highlights the importance of the clinician maintaining an open mind to differential diagnoses and details a technique for surgical removal of a tooth with difficult access.